Copper‐Catalyzed Enantioselective Allylic Alkylation with a γ‐Butyrolactone‐Derived Silyl Ketene Acetal. Issue 5 (16th December 2019) - Jette, Carina I.; Tong, Z. Jaron; Hadt, Ryan G.; Stoltz, Brian M.
Abstract: Herein, we report a Cu‐catalyzed enantioselective allylic alkylation using a γ‐butyrolactone‐derived silyl ketene acetal. Critical to the development of this work was the identification of a novel mono‐picolinamide ligand with the appropriate steric and electronic properties to afford the desired products in high yield (up to 96 %) and high ee (up to 95 %). Aryl, aliphatic, and unsubstituted allylic chlorides bearing a broad range of functionality are well‐tolerated. Spectroscopic studies reveal that a Cu I species is likely the active catalyst, and DFT calculations suggest ligand sterics play an important role in determining Cu coordination and thus catalyst geometry. Abstract : A Cu‐catalyzed enantioselective allylic alkylation using a γ‐butyrolactone‐derived silyl ketene acetal as a nucleophile is reported. Critical to the development of this work was the identification of a novel mono‐picolinamide ligand with the appropriate steric and electronic properties to afford the desired alkylation products in high yields and high levels of enantiomeric excess.